Agricultura familiar: um estudo de caso sobre o desenvolvimento sustentável e a produtividade - Reinehr, Claudia Lais (2015)
This study has like objective, to investigate, through a case study in a property of family farms, if, the introduction of process of technology and innovation, sustainable production practices, of administrative management and of costs, promotes satisfactory results. The family farms is set in a new scenario, where the technologies need to occupy their spaces to that small producers can to became competitive in the market. Thus, it was apply a questionnaire with the property s farmers and the technician that attend on the property. With the direct observation and documental analysis it was sought identify the property characteristics, like as, if they are realized sustainable practices, has farmers have access to technology and innovation, if the management is practiced, analyzing if theses practices lead to satisfactory results for the producers. The results obtain on the search show that the farmers develop sustainable practices, because, even if some practices are not sustainable, the most of them, are sustainable (80%). The are access to technology and innovation consider the results of their actions and their work in eleven years satisfactory, because they meet family social demands. Gaps were identified with respect to the management, the farmers understand what is management, but, they do not use the administrative tools to manage their property. The financial results are above financial investments and they are the result of cultural behavior, commitment, their love for job, desire to evolve and overcome found in farmers.